دور إستخدام نماذج تسيير المخزون في تجسين أداء المؤسسات الجزائرية دراسة حالة عيادة خاصة بولاية بسكرة - حوحو, فطوم; دريدي, أحلام (جامعة الوادي - University of Eloued, 2018)
The aim of this study is to know the role of using operational research models in improving the performance of Algerian institutions. The focus is on the method of inventory management models, which helps in a scientific way to improve the standards of performance of Algerian institutions. The purpose of this study is to formulate and solve a model using QM for Windows. This study was implemented in a special clinic in Biskra in 2017. The study presented an alternative model to improve the current situation in the institution under study. All the indicators of performance, and therefore this study proved that it is possible to use the models of inventory management in improving the performance of Algerian institutions, and therefore recommends the need to develop a special section of research operations in Algerian institutions.
مقال
Keywords: نماذج بحوث العمليات، نماذج تسيير المخزون ، الأداء; Operations Research Models, Inventory Management Models, Performance